7y-3+y=-(y+9y)

Simple and best practice solution for 7y-3+y=-(y+9y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-3+y=-(y+9y) equation:


Simplifying
7y + -3 + y = -1(y + 9y)

Reorder the terms:
-3 + 7y + y = -1(y + 9y)

Combine like terms: 7y + y = 8y
-3 + 8y = -1(y + 9y)

Combine like terms: y + 9y = 10y
-3 + 8y = -1(10y)

Remove parenthesis around (10y)
-3 + 8y = -1 * 10y

Multiply -1 * 10
-3 + 8y = -10y

Solving
-3 + 8y = -10y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '10y' to each side of the equation.
-3 + 8y + 10y = -10y + 10y

Combine like terms: 8y + 10y = 18y
-3 + 18y = -10y + 10y

Combine like terms: -10y + 10y = 0
-3 + 18y = 0

Add '3' to each side of the equation.
-3 + 3 + 18y = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 18y = 0 + 3
18y = 0 + 3

Combine like terms: 0 + 3 = 3
18y = 3

Divide each side by '18'.
y = 0.1666666667

Simplifying
y = 0.1666666667

See similar equations:

| 3(2n-4)=5(n+2) | | 9y-2y^2=10 | | n^3=8 | | 4+4=6 | | n^2=4 | | y^2-4.5y-5=0 | | 5*n+7=89 | | 4x-7=3(2x-3) | | y^2=2 | | 2(4x+3)-4=3x+11+2x | | x+4+X-1= | | y^2+4y+3=0 | | 7a+4(a+3)=33 | | -3b+14=-4 | | x+20=3x+6 | | 5t^2-7t=60 | | x=2,5/10 | | 1x=1/1 | | 4(2x-1)+8=2x | | (c+o+l+l+e+e+n)*(c+o+l+l+e+e+n)=x | | 5+3G=3+5 | | x+q=q^5+13840934 | | X^4-9X^2-81=0 | | 5x=240 | | -2(2+-2b)+b=8 | | 5h-2=10 | | 4(5x-8)=88 | | -6x-3.4=3x+2.0 | | 6xy(3x^2-4y^2)= | | 4x+3.0=-4x-2.6 | | 4(2s)-3s=15 | | 5x=260 |

Equations solver categories